Citizenship and Authority "Having a Duty or Asking for a Right" - Seif al-Deen, Abdullah Mustafa (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
Citizenship is identified in terms of a constellation of rights intermingled with social and political duties including the right to vote, enjoying the public liberties related to political practice, and occupying general posts, etc. Such contribution is based on the principle of equality, and acknowledging the full membership of the individual within his community. The citizen, however, is obsessed by elevating the civilization of his homeland, and continuing its history of progress and modernity. Authority is a political and economic concept the existence of which requires the status of human conglomeration. Hypothetically, it should be elected democratically. Its function is to avail multifaceted services in order to guarantee the continuity of society and government, thus, the citizen and the state. Henceforward, authority types basically spring from the variety of services that are supposed to provide to society and citizens. The practical applicability of the principle of citizenship is likely to ensure the strength of states and the availability of the elements of its independent existence, the sovereignty of its authority, its citizens' monitoring of its treasures and wealth, its officials' keenness to keep it progressed and elevated, and their dedication to keep it upright. Accordingly, what is the relationship between rights and duties? What is the relationship of each of them to citizenship and authority?